2017
DOI: 10.5603/ait.2017.0040
|View full text |Cite
|
Sign up to set email alerts
|

Tomografia impedancyjna w diagnostyce i monitorowaniu zaburzeń funkcji płuc na oddziale intensywnej terapii — opis przypadku i przegląd piśmiennictwa

Abstract: The aim of this paper is to describe the possibility of using Electrical Impedance Tomography (EIT) as a treatment monitoring tool in the ICU. It was based on case report and literature review. A 19-year-old female was admitted to ICU due to severe acute respiratory distress syndrome. Despite aggressive treatment there was no improvement. We decided to use EIT in the monitoring of treatment because of difficulties in transporting the patient to the radiology department in order to perform a control CT scan. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Its unusual high temporal resolution makes EIT ideal to be used in fast-acting settings with a need for fast decision making, such as in intensive care units (ICUs). [3][4][5] It is undoubtfully clear that EIT may pose as the primary imaging tool for ARDS in intensive and critical care settings. 5 History of EIT EIT device is first introduced in the 1980s and quickly regained interest between scientific communities.…”
Section: Introductionmentioning
confidence: 99%
“…Its unusual high temporal resolution makes EIT ideal to be used in fast-acting settings with a need for fast decision making, such as in intensive care units (ICUs). [3][4][5] It is undoubtfully clear that EIT may pose as the primary imaging tool for ARDS in intensive and critical care settings. 5 History of EIT EIT device is first introduced in the 1980s and quickly regained interest between scientific communities.…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions to the above problems may be the EIT method, which has proven to be an effective means of organizing the treatment process in intensive care units, especially in the AVL implementation [16][17][18]. For example, article [16] describes the possibility of using the EIT as a treatment monitoring tool in the intensive care unit due to the difficulty of transporting a patient to the radiology department for the control CT. Studies in article [16] have shown that the use of the EIT makes it possible to assess the EIT method is solution ofaninverse problem of reconstructing the conductivity field of an object's cross-section, determined by the plane of the electrodes' attachment. The EIT method was most common during bedside monitoring of lungs of the patients in an intensive care unit and of those connected to devises of respiratory support of external breathing function [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical impedance tomography (EIT) is a noninvasive effective method to reconstruct and visualize the conductivity distribution in biological objects from the results of electrical measurements on its surface [1][2][3][4][5][6][7][8][9][10][11][12][13]. In the general case, the investigated object (IO) is connected to one or more sources of high frequency electrical current through electrodes placed on its surface, and measured the voltages at the electrodes (where i is the number pair of injecting electrodes, j is the number of measuring electrode) [14].…”
Section: Introductionmentioning
confidence: 99%